Toponymic MORPHOLOGY OF THE PROVINCE OF Pallasca - Del Carmen Cuba, Maria (2005)
This article deals with the description ofplace names (in Pallasca, Ancash)said to derive from Andean originallanguages such as Culli, Quechua andAimara. The names are further classified in simple, compound and derived.Also, the structures of such words are analyzed.